Women as their “own liberators”: creating new frames through film - Mushore, Washington (Unkown, 2016)
The image and depiction of women in the media has long been a subject of concern. Females have been outnumbered by males for a very long time in almost all forms of mainstream media and those who do appear were often portrayed in very negative stereotypical ways. Women were more likely to be shownin the home, performing domestic chores such as laundry or cooking; as sex objects who exist primarily to service men; as victims who cannot protect themselves and as the natural recipients of beatings, harassment, sexual assault and murder. Men and boys were always stereotyped by the media as being masculine and masculinity being associated with machismo, independence, competition, emotional detachment, aggression and violence. In advertising, for instance, girls were and are always shown as being endlessly preoccupied by their appearance and fascinated primarily by dolls and jewellery, while boys are encouraged to play sports and become engrossed by war play and technology. The aim of this paper is to show that in Zimbabwe issues of gender equality are now beginning to take place as evidenced by the new languages or frames that are originating from women which are now challenging male frames. The paper argues that it is only through ‘feminine' vocabulary or frames that women can emancipate themselves from male dominance. Women should become their own liberators. Thus, if they want to reposition themselves in society they should do away with the male vocabulary or frames and create their own frames as will be exemplified through the Zimbabwean documentary film The Extra Mile (2015).